Nevus of Striated Muscle: A New Clinicopathologic Entity. Issue 2 (March 2014) - Ormaechea, Nerea; Hernández‐Martín, Angela; Happle, Rudolf; Colmenero, Isabel; Torrelo, Antonio
Abstract A 3‐month‐old boy presented with a congenital atrophic plaque on his right palm. On histopathologic examination, bundles of mature striated muscle were noted replacing the subcutis and extending into the dermis, without any other mesenchymal component seen. We have not been able to find a similar previously reported case. We propose the name nevus of striated muscle for this congenital, well‐circumscribed cutaneous lesion composed exclusively of mature skeletal muscle.